"You Get the Great Feeling That You're Being Heard But in the End You Realize That Things Will Be Done Differently and in Others' Favor": An Experimental Investigation of Negative Effects of Participation in Evaluation. (March 2019) - Froncek, Benjamin; Rohmann, Anette
Practical-participatory evaluation is often considered an effective approach to enhancing evaluation use. Despite this generally positive connotation, potential negative effects of participatory evaluation have also been discussed in the literature but never empirically investigated before. Drawing upon the social–psychological procedural justice literature, we assumed that stakeholders' perceptions about the justice of an evaluation might explain possible negative effects of participatory evaluation on evaluation use. Negative effects of participatory evaluation on instrumental and conceptual use were explored in two experiments (Study 1: N = 85; Study 2: N = 78). The results show that negative effects of participation on evaluation use are mediated by stakeholders' justice perceptions. Implications of the present research include considering stakeholders' socioemotional needs, negotiation, and transparency when conducting participatory evaluation.